Correction: Unraveling the effects of linker substitution on structural, electronic and optical properties of amorphous zeolitic imidazolate frameworks-62 (a-ZIF-62) glasses: a DFT study. Issue 28 (29th April 2020) - Xiong, Mo; Zhao, Xiujian; Yin, Guanchao; Ching, Wai-Yim; Li, Neng
Abstract : Correction for 'Unraveling the effects of linker substitution on structural, electronic and optical properties of amorphous zeolitic imidazolate frameworks-62 (a-ZIF-62) glasses: a DFT study' by Mo Xiong et al., RSC Adv., 2020, 10, 14013–14024, ; DOI: 10.1039/C9RA09977H .